Ukrepi za obravnavo otroka z okužbo zgornjih dihalnih poti - Cilar Budler, Leona (Obzornik zdravstvene nege, 2021)
Introduction: Upper respiratory tract infections are common infections in children and are a frequent reason for dropping out of school, visiting a doctor and for unnecessary healthcare costs. The purpose of this research is to review, analyze and synthesize the existing literature on the measures for the treatment of children with upper respiratory tract infection. Methods: A descriptive method was used. The literature search was conducted in the period from December 2019 to January 2020 in the Medline and CINAHL databases. The process of searching and analyzing the literature is shown using a PRISMA diagram. The results were analyzed according to the characteristics of the studies and classified according to the level of evidence. The results were synthesized using content analysis. Results: Out of 1845 identified hits, 18 were included in the final analysis. We identified 10 categories: knowledge, identification of upper respiratory tract infection, prescribing and using antibiotics, using non-prescribed drugs in the home environment, using prescribed drugs in the home environment, using prescribed drugs in the hospital, social isolation, unproven drug success, activities of healthcare professionals to prevent or treat upper respiratory tract infections, child and parent-focused treatment. We identified three categories: health education, treatment, and measures to improve health care, nursing, and care. Discussion and conclusion: For quality healthcare treatment of children with upper respiratory tract infections, a child- and family-oriented, holistic and safe approach is needed. Measures in the interdisciplinary medical treatment of children should be based on scientific evidence. In addition to appropriate treatment and measures, it is important that training for children and parents is also provided.
Keywords: dihala; health education; infections; nursing team; okužbe; otroci; parents; pediatric nursing; starši; zdravstvena nega; zdravstvena vzgoja